2021
DOI: 10.1155/2021/4913824
|View full text |Cite
|
Sign up to set email alerts
|

Regression-Based Prediction of Power Generation at Samanalawewa Hydropower Plant in Sri Lanka Using Machine Learning

Abstract: This paper presents the development of models for the prediction of power generation at the Samanalawewa hydropower plant, which is one of the major power stations in Sri Lanka. Four regression-based machine learning and statistical techniques were applied to develop the prediction models. Rainfall data at six locations in the catchment area of the Samanalawewa reservoir from 1993 to 2019 were used as the main input variables. The minimum and maximum temperature and evaporation at the reservoir site were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, the study offers valuable insights, particularly regarding the near future, that can aid policymakers in the water sector when making decisions related to Sustainable Development Goals, specifically Clean Water & Sanitation (SDG 6), Climate Action (SDG 13) and SDG15 (Life on Land) [ 70 ]. Moreover, the establishment of a new run-of-the-river hydropower plants in the region has the potential to create employment opportunities for the local community [ [71] , [72] , [73] ]. This initiative can contribute to achieving the indicator SDG 1.1, which aims to eradicate extreme poverty for all people everywhere, falling under the broader goal of SDG 1 (No Poverty).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study offers valuable insights, particularly regarding the near future, that can aid policymakers in the water sector when making decisions related to Sustainable Development Goals, specifically Clean Water & Sanitation (SDG 6), Climate Action (SDG 13) and SDG15 (Life on Land) [ 70 ]. Moreover, the establishment of a new run-of-the-river hydropower plants in the region has the potential to create employment opportunities for the local community [ [71] , [72] , [73] ]. This initiative can contribute to achieving the indicator SDG 1.1, which aims to eradicate extreme poverty for all people everywhere, falling under the broader goal of SDG 1 (No Poverty).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, four statistical error criteria comprising mean absolute error (MAE), root mean square error (RMSE), mean absolute percentage error (MAPE), and correlation coefficient (R) are used for assessment of the goodness of a model to estimate an observed output variable. Their calculation methods are as follows [51][52][53]:…”
Section: Error Analysismentioning
confidence: 99%
“…The major crop cultivation seasons in SL thus relies on seasonal rainfall, where the primary cultivation season of Maha (October–March) begins with the onset of OND rainfall, whearas the secondary cultivation season of Yala (April–September) begins with the onset of AMJ rainfall (Burt & Weerasinghe, 2014; Zubair, 2002). In addition, hydropower, which is one of the major sources contributing to the national power supply in SL (Dilini et al, 2014; Ekanayake et al, 2021), also depends on the amount of seasonal rainfall. However, several studies have revealed the potential impacts of extreme rainfall on agriculture and the economy of SL (Withanachchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%